2011
DOI: 10.1111/j.1447-0756.2011.01624.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of lower genital tract infections among women in Beijing, China

Abstract: Improving women's living standards and knowledge regarding reproductive health issues can help decrease the incidence of LGTIs and cervical intraepithelial neoplasia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 17 publications
2
11
0
2
Order By: Relevance
“…These data also support the finding that young adults are high-risk groups that are being infected with CT [34]. Moreover, our study have shown that Trichomonas vaginalis is not considered to be a co-factor of HPV in lesion progression to CC, which was essentially in agreement with other study [6]. …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These data also support the finding that young adults are high-risk groups that are being infected with CT [34]. Moreover, our study have shown that Trichomonas vaginalis is not considered to be a co-factor of HPV in lesion progression to CC, which was essentially in agreement with other study [6]. …”
Section: Discussionsupporting
confidence: 93%
“…Previous studies have reported the prevalence of 11.4–21% for the most common LGTIs in women of reproductive age [6]. However, with the development of new medical diagnostic techniques, more gynecologists in China have observed that the incidence of LGTIs has increased in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…Similar findings were observed in a study in the UK where infection with chlamydia or bacterial vaginosis was independent risk factor for vaginal HPV infection [15]. Such associations are also seen from LMICs such as China where higher RTIs were associated with the incidence of cervical intraepithelial neoplasia (CIN) and HPV infection [16]. Another study from Beijing observed high rates of CIN among women with bacterial vaginitis [17].…”
Section: Introductionsupporting
confidence: 71%
“…Candidíase vulvovaginal é a segunda causa mais frequente de vaginite e o diagnóstico requer a precisa identificação laboratorial da Candida spp. envolvida [9][10][11][12][13][14][15][16][17][18][19][20][21][22] .…”
Section: Discussionunclassified
“…Ainda que não seja considerada uma infecção de transmissão sexual 11 , cerca de 25% dos parceiros sexuais de mulheres com CV albergam cepas idênticas de Candida em seu sulco bálano prepucial, e a infecção é motivada possivelmente por traumas da mucosa vaginal durante o ato sexual e/ou pelo efeito imunodepressor do sêmen [11][12][13][14][15][16][17] .…”
Section: Introductionunclassified